Abdominal stab wound in A Pregnant woman resulting in Evisceration, Uterine Perforation and Fetal Chest Injury: A Case Report and Literature Review - Ousmana Oumarou; Tchuenkam W Landry; Njweipi C Joe; Festus T Wirwah; Bisay S Ulrich; Engbang N Jean-Paul (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Introduction: trauma is common in pregnancy; it affects one in twelve pregnancies. Abdomen represents the third anatomical region of the body most affected after the limbs and head. As pregnancy evolves, uterus increases in size and goes beyond the pelvic cavity; exposing the uterus to trauma and penetrating injuries in particular. Penetrating abdominal trauma in pregnancy requires a rigorous clinical evaluation to establish a complete assessment of obstetric and non-obstetric lesions. It is an obstetrical emergency whose management depends on the abnormalities found. In case of major trauma, it is essentially carried out in a trauma center, with a multidisciplinary team to improve the maternal and fetal prognosis. Case presentation: the authors report the case of a 28-year-old black woman, semi-Bantu, at 30 weeks gestation. She was referred to the emergency department of Douala Laquintinie Hospital for a penetrating wound of the abdomen after being stabbed at home. There were bowels protruding from the stabbed abdomen. The initial clinical assessment revealed hemodynamic instability, evisceration associated with bowel perforation, absence of active fetal movements, and absence of fetal heart sound from Doppler. An emergency laparotomy was performed. At the end of the surgical intervention, the following lesions were indentified: penetrating wound of the abdomen with evisceration, intestinal perforation, uterine perforation, fetal penetrating chest injury and fetal death. Conclusion: this case report focuses on the spectrum of non-obstetric, obstetric and fetal injuries that may occur as a result of a penetrating stab wound in a pregnant woman.